When we die: Chiasma in the context of poetry and popular genres - Pavel Matejovič (Slovenska Literatura)
The paper is inspired by essays on literature and theoretical texts by the Slovak literary scholar Fedor Matejov (b.1954). It traces his preferred rhetorical figures, identifying chiasmus and fragmentation as fundamental elements of his literary-theoretical framework. Matejov uses chiasma not only as a rhetorical figure with evocative power, but also as a metonymic tool to describe contemporary poetics and cultural processes. Through examples such as the poetry of Miroslav Válek and Milan Rúfus, and the polemics of the late 1950s concerning the “poet's right to sadness,” the paper traces the transformations in literary-theoretical thinking about death and extinction. Matejov’s interpretations of poetry provide the basis for reflections in which the concept of “high” poetry is subversively contaminated by popular genres (science fiction) and dystopia. The article shows that science fiction literature can function as a genre chiasma to fiction, that is, that modern poetry, philosophy, and science fiction can coexist in a Lotmanian way in the space of literary discourse. Being and time are chiastically manifested through various genre invariants.